2020
DOI: 10.7498/aps.69.20191141
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation on dynamic behavior of single droplet impcating normally on dry sphere

Abstract: The phenomenon that droplets impacting on the solid surface is ubiquitous in industrial applications such as spray cooling, spray painting, ink-jet printing, and fuel-air mixing internal combustion engines. The dynamic of droplet impacting on solid surface has been a hot topic in the area of fluid mechanics. Most of the existing experimental studies focused on the droplet impacting on flat or cylinder surface whereas the droplet impacting on a dry sphere surface, especially its effect from the sphere curvature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…When the wall temperature is -25~5ႏ, there will be rebound and crushing phenomenon. In their study, Tang et al [8] looked at how a droplet moves when it hits a sphere at a high Weber number, and the results showed that when the curvature į 0.167 mm -1 , a completely dynamic process occurs after the impact; when the curvature 0.167 mm -1 į 0.2 mm -1 , droplets cover almost the entire surface; when the curvature į 0.2 mm -1 , some of the droplets will slide off the sphere.…”
Section: Introductionmentioning
confidence: 92%
“…When the wall temperature is -25~5ႏ, there will be rebound and crushing phenomenon. In their study, Tang et al [8] looked at how a droplet moves when it hits a sphere at a high Weber number, and the results showed that when the curvature į 0.167 mm -1 , a completely dynamic process occurs after the impact; when the curvature 0.167 mm -1 į 0.2 mm -1 , droplets cover almost the entire surface; when the curvature į 0.2 mm -1 , some of the droplets will slide off the sphere.…”
Section: Introductionmentioning
confidence: 92%